Brand Loyalty of Customers in Smartphone Brands - Santhosh Kumar, S.; Menon, Rahul P. (Indian Journal of Marketing, 2017)
The smartphone, one of the priceless contributions of mobile technology, has now resulted in a situation of cut throat competition between different handset manufacturers who are trying their level best to outsmart their competitors. Brand loyalty, which is a crucial factor influencing purchase decision of smartphone users, is assessed in this particular scenario. The assessment of brand loyalty for the present study was done with reference to a Swedish study (Ahmed & Moosavi, 2013) by taking into account the overall brand loyalty score generated from the five constructs such as brand image (bi), brand quality (bq), brand experience (be), brand switching cost (bsc), and customer satisfaction (cs). Apple topped the list with the highest brand loyalty score followed by Asus, Blackberry, LG, Samsung, Motorola, Micromax, Nokia/Microsoft, Sony, Xiaomi, Lenovo, Huawei, and HTC in the study conducted among IT employees. The statistically significant difference found in the brand loyalty scores of different smartphone brands signals the manufacturers to seriously focus on brand loyalty building to cope up with the cut throat competition and to ensure their long-term growth and survival. The manufacturers should concentrate more on areas such as image building, manufacturing quality products, and ensuring customer satisfaction.